2011
DOI: 10.1039/c1ee01116b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in capture of carbon dioxide using alkali-metal-based oxides

Abstract: Carbon dioxide (CO 2 ) is a major greenhouse gas and makes a significant contribution to global warming and climate change. Thus CO 2 capture and storage (CCS) have attracted worldwide interest from both fundamental and practical research communities. Alkali-metal-based oxides such as alkalimetal oxides, binary oxides, and hydrotalcite-like compounds are promising adsorbents for CO 2 capture because of their relatively high adsorption capacity, low cost, and wide availability. They can also be applied to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
222
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 345 publications
(223 citation statements)
references
References 136 publications
0
222
1
Order By: Relevance
“…This value is slightly larger than the highest value reported so far at RT and 1 bar for microporous materials (27.5 mass% in the metal organic frameworks Mg 2 (dobdc) and HKUST-1), 28 where CO 2 is molecularly adsorbed in the material pores. Nevertheless, this value is about one half of that reported for the most performing oxidic systems, 7 although in that case the formation of carbonates and bicarbonates species requires to adopt very high temperatures (e.g. CaO/Al 2 O 3 , 68 mass% at 1 bar and 600°C).…”
Section: Fast Carbon Dioxide Recycling By Reaction With -Mg(bhmentioning
confidence: 87%
See 2 more Smart Citations
“…This value is slightly larger than the highest value reported so far at RT and 1 bar for microporous materials (27.5 mass% in the metal organic frameworks Mg 2 (dobdc) and HKUST-1), 28 where CO 2 is molecularly adsorbed in the material pores. Nevertheless, this value is about one half of that reported for the most performing oxidic systems, 7 although in that case the formation of carbonates and bicarbonates species requires to adopt very high temperatures (e.g. CaO/Al 2 O 3 , 68 mass% at 1 bar and 600°C).…”
Section: Fast Carbon Dioxide Recycling By Reaction With -Mg(bhmentioning
confidence: 87%
“…CaO/Al 2 O 3 , 68 mass% at 1 bar and 600°C). 7 The uptake is completely irreversible, as demonstrated by the second isotherm, indicating that almost the whole material was reacted at the end of the first absorption isotherm. Also in this case, the key-role of the surface area is evident by comparison with the data collected on the  phase.…”
Section: Fast Carbon Dioxide Recycling By Reaction With -Mg(bhmentioning
confidence: 99%
See 1 more Smart Citation
“…1), two families of GAM which at present are being investigated also very thoroughly [70][71][72][73][74]. For the sake of focus, other important mechanisms exploited in gas storage and sequestration processes (e.g., gas binding in bulk chemical form and thermodynamic destabilization of nanocrystals and clusters [75][76][77][78][79]) and related families of materials (e.g., metal oxides and binary and ternary hydride compounds [80][81][82][83][84][85]), will not be discussed exhaustively in the present work.…”
Section: F Focus and Organization Of This Reviewmentioning
confidence: 99%
“…At those conditions, it can be shown that CO 2 sequestration turns out to be effective when the strength of the gas-GAM interactions roughly amounts to 2.0 eV/molecule. For this, consider the inverse calcination reaction, CaO + CO 2 → CaCO 3 , to be a model of a typical pre-combustion CCS process [77][78][79]. The Gibbs free-energy balance of this reaction has been approximated by the function ∆G = −1.83 + 0.0016 · T eV/molecule, where T represents the temperature (expressed in Kelvin) [117].…”
Section: Carbon Capture and Sequestrationmentioning
confidence: 99%